Photovoice for post-occupancy evaluation: students explore health in a sustainable school - Marley, Jenifer, author; Nobe, MaryEllen, advisor; Clevenger, Caroline, committee member; Banning, James, committee member (Colorado State University. Libraries, 2012)
This study engaged six fourth grade students who attend a LEED® gold certified school, Bethke Elementary School located in northern Colorado, as co-researchers to explore their perspectives about health in their school environment. The methodology used in the study was developed as a participatory post-occupancy evaluation (PPOE) method, an innovative adaptation of an existing participatory visual research method, photovoice. The study documents a PPOE method that provided students an opportunity to voice their perspectives through the use of photography, digital story-telling and semi-structured focus group discussions. The method emphasizes the first-hand perspective of building occupants, in this case children. The study raises awareness about the opportunities green schools have to facilitate children's health. The students identified fourteen physical environmental attributes that they perceive as facilitating health according to their own conceptual definition established during a focus group discussion at the beginning of the study. Two of the fourteen attributes emerged as the most significant, including community connectivity and a connection to nature. Additionally, the research discusses social sustainability in relationship to an internationally recognized health framework. Five themes emerged in the study including stewardship; a desire for learning; participation in recreation, physical activities, and relaxation; sense of belonging to a community; and cultural values and attitudes of well-being. The study addresses shortcomings of existing post-occupancy evaluation techniques, and proposes an interdisciplinary, qualitative approach to the evaluation of children's environments. Building professionals, school facilities planners, school administrators, as well as others interested in the health and well-being of children in relation to their everyday environments will find this study meaningful.
Keywords: green schools; sustainable building; social sustainability; post-occupancy evaluation; health